Bacteroides plebeius improves muscle wasting in chronic kidney disease by modulating the gut‐renal muscle axis. Issue 24 (2nd December 2022) - Pei, Tingting; Zhu, Daoqi; Yang, Sixia; Hu, Rong; Wang, Fujing; Zhang, Jiaxing; Yan, Shihua; Ju, Liliang; He, Zhuoen; Han, Zhongxiao; He, Jinyue; Yan, Yangtian; et al.
Abstract: Chronic kidney disease (CKD) affects approximately 10% of the global population. Muscle atrophy occurs in patients with almost all types of CKD, and the gut microbiome is closely related to protein consumption during chronic renal failure (CRF). This study investigated the effects of Bacteroides plebeius on protein energy consumption in rats with CKD, and our results suggest that Bacteroides plebeius may combat muscle atrophy through the Mystn/ActRIIB/SMAD2 pathway. A total of 5/6 Nx rats were used as a model of muscle wasting in CKD. The rats with muscle wasting were administered Bacteroides plebeius (2 × 10 8 cfu/0.2 ml) for 8 weeks. The results showed that Bacteroides plebeius administration significantly inhibited muscle wasting in CKD. High‐throughput 16 S rRNA pyrosequencing revealed that supplementation with Bacteroides plebeius rescued disturbances in the gut microbiota. Bacteroides plebeius could also enhance the barrier function of the intestinal mucosa. Bacteroides plebeius may modulate the gut microbiome and reduce protein consumption by increasing the abundance of probiotics and reducing damage to the intestinal mucosal barrier. Our findings suggest that Bacteroides plebeius may combat muscle atrophy through the Mystn/ActRIIB/SMAD2 pathway.